2020
DOI: 10.29271/jcpsp.2020.01.73
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Humeral Shaft Fracture Treated with Intramedullary Nail and Plate Fixation

Abstract: Objective: To compare the results of the intramedullary nail (IMN) and compression plate fixation performed for humeral shaft fracture as to determine a better option out of the two.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Intramedullary nailing is a simple technique in contrast to other interventions like plating. According to Wang Y's study [10], the procedure is less invasive thus decreasing the duration of hospital stay as mentioned in this study as well. According to the literature [11], patients having quicker healing periods were found to be the ones that were managed via closed reduction, like in the case of Intramedullary nailing fixation that hardly needs open reduction.…”
Section: Discussionmentioning
confidence: 53%
“…Intramedullary nailing is a simple technique in contrast to other interventions like plating. According to Wang Y's study [10], the procedure is less invasive thus decreasing the duration of hospital stay as mentioned in this study as well. According to the literature [11], patients having quicker healing periods were found to be the ones that were managed via closed reduction, like in the case of Intramedullary nailing fixation that hardly needs open reduction.…”
Section: Discussionmentioning
confidence: 53%
“…Another study by Wang Y et al [22] demonstrated that in plating group overall complications was found in 50% patients while in IML group 23.1% patients developed complications. Arun KN et al [23] reported in their study that only 10% patients showed delayed union who were treated with dynamic compression plating.…”
Section: Discussionmentioning
confidence: 94%
“…Altogether, the 43 studies investigated comprised 7688 patients with humeral shaft fractures. Eleven studies were randomised controlled trials (level II; 25.6%) (19, 20,21,22,23,24,25,26,27,28,29), 5 were prospective non-randomised case-control studies (III; 11.6%) (30,31,32,33,34), and 27 were retrospective cohort studies (IV; 62.8%) (6,8,9,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58). Twentyseven studies compared IM with ORIF (6,19,20,22,24,25,26,27,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Twenty-four studies (8 level II (19,20,22,25,26,27,28,29), 3 level III (30,31,33), 13 level IV (6,39,40,42,47,48,52,53,54,55,56,57,58)) reported on non-union risk for IM vs ORIF. In three (47,48,58) of these studies, no event was reported in either arm, wherefore these were excluded from the meta-analysis.…”
Section: Im Vs Orifmentioning
confidence: 99%
See 1 more Smart Citation